Revitalisasi Adab Murid terhadap Guru Menurut Imam Ghazali, Imam Az Zarnuji dan KH Hasyim Asy’ari - Fikri Fathul Aziz (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This study aims to examine the values of etiquette (adab) of students towards teachers as viewed by three prominent Islamic scholars: Imam Ghazali, Imam Az-Zarnuji, and Imam An-Nawawi. Etiquette towards teachers is considered a fundamental aspect of the teacher-student relationship in Islamic education, which emphasizes not only academic achievement but also moral values and ethics. Imam Ghazali, in his works, stresses the importance of respect, humility, and sincere intention in learning. Imam Az-Zarnuji, in his book Ta'lim al-Muta'allim, offers practical guidelines on student etiquette, including how to speak and behave appropriately towards teachers. Meanwhile, Hadrotus Syaikh Hasyim Asy’ari, in Adabul Alim Wal Muta'allim, advises students to always maintain proper manners with their teachers as a form of respect for both the knowledge and its possessor. This research employs a qualitative approach with content analysis to explore and compare the views of these three scholars regarding student-teacher etiquette. The findings reveal that, despite differences in expression and detail, all three scholars agree on the significance of etiquette as a foundational element in the learning process. These values of etiquette include politeness, exemplarity, respect, and loyalty in the pursuit of knowledge. This study is expected to contribute to the development of Islamic education, particularly in strengthening the harmonious relationship between students and teachers based on the etiquette values espoused by these scholars.